Speak Up To Innovate: How Psychological Safety Drives Innovative Work Behavior Through Knowledge Sharing - Fajar Eryanto Septiawan (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study examines the role of psychological safety in fostering innovative work behavior, with knowledge sharing as a mediating variable. Drawing on Social Exchange Theory, the research argues that when employees feel safe to express ideas without fear of negative consequences, they are more likely to share knowledge, which is an essential process for innovation. Data were collected from 150 employees working in service-sector organizations in Bandung through a structured questionnaire using a 5-point Likert scale. Results analyzed with Structural Equation Modeling with Partial Least Squares (SEM-PLS) revealed that psychological safety significantly enhances knowledge sharing and innovative work behavior. Furthermore, knowledge sharing mediates the relationship between psychological safety and innovative work behavior. These findings highlight that a supportive and open environment encourages employees to exchange ideas and collaborate, thereby promoting creativity and innovation. The study contributes to organizational behavior literature by demonstrating that psychological safety functions not only as an interpersonal climate but also as a foundation for collective innovation.